Influence of digital learning tools and social networking services on learners’ academic achievement in National Open University of Nigeria (2021)
The paper examined the influence of learning tools and social networking services on learners’ academic achievement in National Open University of Nigeria. The descriptive survey research design was adopted while a sample size of 100 respondents were randomly for the study. A13 items questionnaire titled: Perceived Use of Social Networking Services (PUSNSI) was used for data collection. Data were analyzed using simple percentage of frequency count, mean and standard deviation. The findings revealed that out of the five variables of Facebook, Youtube, Zoom, Kahoot and WhatsApp; only Zoom and WhatsApp significantly contributed to learners’ academic achievement in institution. Therefore, in order to achieve vision and mission of distance education in Nigeria, there is the need to raise the level of awareness and utilization of learning tools and social networking services in the institution.